2016
DOI: 10.1038/cddis.2016.226
|View full text |Cite
|
Sign up to set email alerts
|

Cereblon negatively regulates TLR4 signaling through the attenuation of ubiquitination of TRAF6

Abstract: Cereblon (CRBN) is a substrate receptor protein for the CRL4A E3 ubiquitin ligase complex. In this study, we report on a new regulatory role of CRBN in TLR4 signaling. CRBN overexpression leads to suppression of NF-κB activation and production of pro-inflammatory cytokines including IL-6 and IL-1β in response to TLR4 stimulation. Biochemical studies revealed interactions between CRBN and TAK1, and TRAF6 proteins. The interaction between CRBN and TAK1 did not affect the association of the TAB1 and TAB2 proteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
48
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 52 publications
2
48
0
Order By: Relevance
“…Luciferase reporter assay was performed as described previously [23][24][25]46]. Briefly, cells were transiently transfected with or without appropriate vectors indicated in each experiment using Lipofectamine 2000 (Thermo Fisher Scientific, 11,668,019) or Neon® Transfection System (Thermo Fisher Scientific, MPK5000).…”
Section: Luciferase Reporter Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Luciferase reporter assay was performed as described previously [23][24][25]46]. Briefly, cells were transiently transfected with or without appropriate vectors indicated in each experiment using Lipofectamine 2000 (Thermo Fisher Scientific, 11,668,019) or Neon® Transfection System (Thermo Fisher Scientific, MPK5000).…”
Section: Luciferase Reporter Assaymentioning
confidence: 99%
“…Cells were then treated with or without LPS (200 ng/ml) for 6 h. Nuclear proteins were then prepared using CelLytic NuCLEAR extraction kit (Sigma, NXTRACT) per the manufacturer's protocol. Activity of transcription factor RELA was determined using Trans AM NFKB transcription factor assay kit (Active Motif North America, 40,596) per the manufacturer's instructions [24,46].…”
Section: Measurement Of Proinflammatory Cytokines and Rela Dna-bindinmentioning
confidence: 99%
“…the AMP-activated protein kinase ␣1 subunit (40), TAK1-TRAF6 (41), and CD147-MCT1 complex (42), where CRBN plays ubiquitin-independent roles in pathway regulation. The mechanistic underpinnings for induced limb deformities in chickens and zebrafish, but not in mice, appears dependent on sequence differences in mouse CRBN (20), which brings into question whether these differences in CRBN render it functionally inactive.…”
Section: Functional Conservation Among Cereblon Sequence Variantsmentioning
confidence: 99%
“…Immunomodulatory drugs (IMiDs), including thalidomide and its structural analogs lenalidomide and pomalidomide, are a class of compounds that can be used to alleviate the inflammatory response. However, how CRBN regulates inflammation has only begun to unfold (41). It has been reported that CRBN binds to the ubiquitination domain of TRAF6 and attenuates the ubiquitination of TRAF6 and TAK1-binding protein 2 (TAB2), leading to suppression of NF-B activation by negatively regulating the Toll-like receptor 4 (TLR4) signaling pathway (41).…”
mentioning
confidence: 99%
“…However, how CRBN regulates inflammation has only begun to unfold (41). It has been reported that CRBN binds to the ubiquitination domain of TRAF6 and attenuates the ubiquitination of TRAF6 and TAK1-binding protein 2 (TAB2), leading to suppression of NF-B activation by negatively regulating the Toll-like receptor 4 (TLR4) signaling pathway (41). This discovery revealed the important nonenzymatic function of CRBN in the regulation of inflammation.…”
mentioning
confidence: 99%